2018
DOI: 10.1017/jfm.2018.918
|View full text |Cite
|
Sign up to set email alerts
|

Slow viscous flow of two porous spherical particles translating along the axis of a cylinder

Abstract: We describe the motion of two freely moving porous spherical particles located along the axis of a cylindrical tube with background Poiseuille flow at low Reynolds number. The stream function and a framework based on cylindrical harmonics are adopted to solve the flow field around the particles and the flow within the tube, respectively. The two solutions are employed in an iterated framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The unknown coefficients in cylindrical harmonics can be solved by constructing equations from boundary conditions. The details have been included in our works [29,30]. By utilizing the spherical harmonics and cylindrical harmonics for the sphere and cylinder, respectively, the total velocity flow field can be obtained using Eq.(3a).…”
Section: Calculation Procedures Based On the Methods Of Reflectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unknown coefficients in cylindrical harmonics can be solved by constructing equations from boundary conditions. The details have been included in our works [29,30]. By utilizing the spherical harmonics and cylindrical harmonics for the sphere and cylinder, respectively, the total velocity flow field can be obtained using Eq.(3a).…”
Section: Calculation Procedures Based On the Methods Of Reflectionsmentioning
confidence: 99%
“…By repeating the process and adding more reflections, the results will converge, as the magnitude of higher reflections decays to zero [29,30]. We can apply any arbitrary number of reflections in our framework when needed for convergence (details of the convergence test are provided in section 2.1.3).…”
Section: Calculation Procedures Based On the Methods Of Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mathematical details of coordinate transformation between the two spheres in spherical coordinates system can be found in our previous work (Yao et al, 2019).…”
Section: Coordinate Transformationmentioning
confidence: 99%
“…They found that increasing Re enhances the effect of the leading sphere on the trailing sphere. Yao et al 33 solved the flow of porous particles moving along the axis of a cylindrical tube and discussed the effect of L and permeability on the interparticle interaction. Zhang et al 35 numerically investigated the interaction between porous particles with the same diameter.…”
Section: Introductionmentioning
confidence: 99%